Building Leadership Capacity in University First Year Learning and Teaching in the Mathematical Sciences : Final Report. - King, Deborah; Cattlin, Joann; Ward, Jo (Office for Learning and Teaching, 2015)
Final report from a project that took a step towards building a vibrant national network of scholars providing leadership in first year learning and teaching in the mathematical sciences. It examined and promoted the unique leadership role of first year coordinators and educators. It built leadership capacity by identifying characteristics of a national first year culture, and by providing the professional development opportunities, mentoring and support mechanisms, to drive excellence in learning and teaching. It developed case studies that articulated the roles of first year coordinators and educators, including expectations, responsibilities and the capabilities needed to effectively lead the complex mathematical offerings required to support a diversity of degree programs including mathematics, engineering, science and commerce. It fostered the development of a coordinated national approach to learning and teaching in first year mathematics.